Gene-environment interactions in Autism Spectrum Disorders (ASD) - Xavier Santos, João (2017)
Objectives: 1. To identify specific exposure patterns to environmental toxicants, potentially involved in ASD etiology, in a dataset of Portuguese children diagnosed with ASD aged 7-9 years; 2. To identify genetic variants interacting with environmental and epigenetic factors; 3. To build a global model that integrates genetic, environmental and epigenetic factors for risk assessment in ASD.